MONTHLY VARIATION CHARACTERISTICS OF WAVE HEIGHT IN NORTH SULAWESI - Ahmad Fadlan; Ricky Daniel Aror; Denny Nugroho Sugianto; Muhammad Zainuri (Waste Technology, 2017)
ABSTRACTIndonesia is a maritime country which most of the territory is ocean, where many people have activities at sea.  Information about variations and characteristics of wave height in some region is very important to support safety and efficiency of the activity. The purpose of the research is to know and analysis the characteristics of the monthly variations of wave height in the water of North Sulawesi. The data used in this study is a surface wind that processed into Windwaves-05 wave model. This model calculates wave height based on energy from surface wind that blows above the sea surface. The research results showed that variations of sea waves in the waters of North Sulawesi generally are closely related to the monsoon wind patterns that occur in Indonesia. When Asian west monsoon in November to April, the average wave height in the waters of North Sulawesi is higher than wave height at Australian east monsoon in May to October.  The highest average wave occurred in January with maximum wave height to 3.5 m and lowest average wave occurred in October with a maximum height to 1.25 m. Generally, the average wave height in the waters which bordering the ocean is higher than the waters close to all major islands.